THE EFFECTIVENESS OF PHALERIA MACROCARPA’S LEAF NANOEMULSION GEL ON STAPHYLOCOCCUS AUREUS BIOFILM THICKNESS (IN VITRO) - Rosa Pratiwi; Feny Nursyaputri; Recita Indraswary; Irma Dewi Ratnawati (Odonto : Dental Journal, 2022)
Background: Periodontal disease often occurs in the oral cavity with 75.6-78.3% at the age of 35-44 years. One of the causes of periodontal disease is the accumulation of Staphylococcus aureus biofilm in the early colonization of the formation of the dental pellicle. Phaleria macrocarpa, also known as Gods Crown, is a traditional plant with antibacterial properties that can be used in the health sector. Nanoemulsion gel technology has the advantage of increasing the stability of the material. Aim the study to determine the ratio of the effectiveness of Phaleria macrocarpa’s leaf nanoemulsion gel 10%, 20%, 30% to decrease Staphylococcus aureus biofilm thickness.Method: This research method was in vitro experimental laboratory research using a post-test control design. Thirty samples were divided into five groups: Phaleria macrocarpa’s leaf nanoemulsion gel 10%, 20%, 30%, positive control using chlorhexidine gluconate 0.2% and negative control using aqua dest. Samples were incubated for 4 and 8 hours. Optical density readings were carried out to see the biofilm thickness after being given a Gods Crown leaves nanoemulsion gel Results: The mean of Phaleria macrocarpa’s leaf nanoemulsion gel, 30%, produced the lowest average optical density value. The incubation time of 4 hours resulted in a lower optical density value than 8 hours. The Kruskal-Wallis was p>0.05 showed there was no difference in biofilm thickness in each group.Conclusion: the effectiveness of the nanoemulsion group of Dewa crown leaf gel with a concentration of 30% was better than the 0.2% chlorhexidine gluconate gel and sterile distilled water group.